Ottoman Provincial Society and the Waqf of Jerusalem, 1703-1831 - Memiş, Şerife Eroğlu, (Middle East and Islamic Studies E-Books Online, Collection 2026., 2026)
This book examines early modern Jerusalem's waqf system through an Ottoman provincial lens, analyzing how diverse social groups engaged with these endowments in judicial contexts. Conceptualizing waqf s-central to the city's socioeconomic fabric and urban identity-as an interconnected " waqf network", the research demonstrates the commodification of waqf offices among elites, and their enduring control over pious foundations. These processes reveal how provincial power structures mediated between imperial standards and local interests. Focusing on notable families who monopolized waqf -related privileges, the work reconstructs Jerusalemite society through multiple frameworks: imperial waqf policies, social hierarchies, notable-commoner relations, and intercommunal dynamics-positioning endowments as both economic assets and instruments of governance. Bu kitap, erken modern dönem Kudüs'ündeki vakıf sistemini Osmanlı taşra perspektifinden incelemekte ve çeşitli sosyal grupların bu vakıflarla hukuki bağlamda nasıl etkileşime girdiğini analiz etmektedir. Kentin sosyo-ekonomik dokusu ve kentsel kimlğinin merkezinde yer alan vakıfları birbiriyle bağlantılı bir "vakıf ağı" olarak kavramsallaştıran araştırma, seçkinler arasında vakıf görevlerinin metalaşması ve bu kesimin hayır kurumları üzerindeki kalıcı denetimlerini ortaya koymaktadır. Bu süreçler, taşradaki güç yapılarının imparatorluk standartlarıyla yerel menfaatler arasında nasıl aracılık ettiğini gözler önüne sermektedir. Vakıfla ilgili ayrıcalıkları tekelleştiren önemli ailelere odaklanan çalışma, Kudüs toplumunu çoklu çerçevelerle yeniden inşa etmektedir: imparatorluk vakıf politikaları, sosyal hiyerarşiler, seçkinler-halk ilişkileri ve cemaatler arası dinamikler. Böylece vakıflar, hem ekonomik varlıklar hem de yönetim araçları olarak konumlandırılmaktadır.